Respuesta :
Answer:
[tex]\left(x^2+3i\right)\left(x^2-3i\right)[/tex]
Step-by-step explanation:
[tex]x^4+9[/tex]
[tex]x^4+9[/tex] can be written as [tex]x^4--9[/tex].
Apply the formula for the difference of two squares.
[tex](a^2-b^2)=(a+b)(a-b)[/tex]
[tex]-9=3i^2[/tex]
[tex]x^4=(x^2)^2[/tex]
[tex](x^2)^2-(3i)^2=(x^2+3i)(x^2-3i)[/tex]
Answer:
(x^2 - 3i) ( x^2 +3i)
Step-by-step explanation:
X^4+9
x^4 - -9
This is the difference of squares (a^2 - b^2) = (a-b)(a+b)
(x^2) ^2 - ( 3i)^2
(x^2 - 3i) ( x^2 +3i)